The Situation of the Health System in Peru to 2021 and the Pending Agenda - Javier Jara, Juan José; Cuadros Salazar, Diego Abraham (American Journal of Management, 2022)
This descriptive research seeks to identify and present the situation of the Peruvian health system in 2021, as well as to propose the schedule pending for the sector, proposing the contrast of the evolution of health spending with the previous periods, comparatively with other countries of the Latin American and European region. The problem of human resources in the sector is analyzed, and finally, the infrastructure gap of the first level of care is identified. It is concluded that the health sector needs a sustained increase in a greater proportion of the general budget of the republic, as well as the decentralization of the PNA.